The Contrived Mutant p53 Oncogene – Beyond Loss of Functions - Sabapathy, Kanaga (Frontiers in Oncology, 2015)
Mutations in p53 are almost synonymous with cancer – be it susceptibility to the disease or response to treatment – and therefore, are a critical determinant of overall survival. As most of these mutations occur in the DNA-binding domain of p53, many of the clinical correlations with mutant p53 have been initially relegated to the loss of its transcription-dependent activities as a tumor suppressor. However, significant efforts over the last two decades have led to the vast knowledge on the potential functions of the mutated p53 protein, which have been attributed to the physical presence of the mutant protein rather than the loss of its wild-type (WT) functions. Beyond the inhibitory effects of mutant p53 on the remaining WT protein that leads to the dominant-negative effect in the heterozygous state, mutant p53’s presence has also been significantly attributed to novel gain-of-functions that lead to addiction of cancer cells to its presence for survival, as well as for their ability to invade and metastasize, elevating it to a contrived oncogene that drives the cancer cells forward. This review will summarize the functional consequences of the presence of mutant p53 protein on cellular and organismal physiology.